2017
DOI: 10.1155/2017/4207301
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectroscopy of Binary Titanium Borides: First-Principles and Experimental Studies

Abstract: Vibrational dynamics of binary titanium borides is studied from first-principles. Polarized and unpolarized Raman spectra of TiB, TiB2, and Ti3B4 are reported along with the experimental spectra of commercial powder and bulk TiB2 containing less than 1 wt.% of impurity phases. The X-ray diffraction spectroscopy, applied for phase composition examination of both bulk and powder materials, identifies only the TiB2 phase. The simulated Raman spectra together with literature data support interpretation and refinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
2
0
Order By: Relevance
“…This peak confirms the presence of B–B bonds in a honeycomb arrangement. Similar peaks were also observed in TiB 2 by Wdowik et al 56 We observed all three peaks in the Raman spectra of nanosheets with a several fold decrease in the intensity. An interesting point to note is that no apparent shift is observed in the peaks compared to those of bulk TiB 2 .…”
Section: Resultssupporting
confidence: 89%
“…This peak confirms the presence of B–B bonds in a honeycomb arrangement. Similar peaks were also observed in TiB 2 by Wdowik et al 56 We observed all three peaks in the Raman spectra of nanosheets with a several fold decrease in the intensity. An interesting point to note is that no apparent shift is observed in the peaks compared to those of bulk TiB 2 .…”
Section: Resultssupporting
confidence: 89%
“…At present, a systematic study that discusses all the vibrational modes of TiB 2 is missing in the literature. A few studies suggest that TiB 2 by itself does not exhibit any Raman active properties, and any peaks observed are due to contamination and sintering aids, which are used in the synthesis of TiB 2 . However, as reported by Pumera and co-workers, metal diborides do exhibit a common E 2g vibration mode due to boron, while the peak position and intensity primarily depend upon metal atoms. Therefore, we anticipate similar peaks in TiB 2 as well. As shown in Figure b, the Raman spectra of bulk and ball milled TiB 2 primarily exhibit three peaksthese can be attributed to B 1g , E g , and A 1g modes, as recently shown for TiB 2 . , These three modes are pictorially depicted in Figure d and explained as follows(i) the B 1g mode corresponds to the out-of-plane vibration of boron atoms along the z -axis, with adjacent atoms vibrating in opposite directions, as explained by Bohnen et al ; (ii) the E g mode corresponds to the in-plane vibration of boron atoms along the xy plane, with adjacent atoms vibrating in opposite directions, as explained by Liu et al for MgB 2 ; and (iii) the A 1g mode corresponds to out-of-plane vibration of boron atoms along the z -axis, with adjacent atoms vibrating in the same direction.…”
Section: Resultssupporting
confidence: 62%
“…Figure 12 a shows the Raman spectra of the at 1600 °C under Argon heat-treated powders C41, BTV and BT. The bands of TiB 2 at 881 cm −1 [ 43 ] and 1573 cm −1 [ 44 ] are weak due to a low Raman activity and the low mass fraction of TiB 2 in the powders BT and BTV. In all the heat-treated powders a similar weak hBN-band can be observed.…”
Section: Resultsmentioning
confidence: 99%